The Liverworts Family Plagiochilaceae In Bukit Barisan Forest Park, North Sumatra - siregar, etti sartina; Sembiring, Christian Hadinata (International Journal of Ecophysiology, 2024)
Bukit Barisan Forest Park at Karo Regency, North Sumatra is a habitat for many species of liverworts, one of them is Plagiochilaceae. However little information about species of Plagiochilaceae reported from the area. This study aims to identify the species of Plagiochilaceae and describe their morphology. The research was conducted from July 2021 to February 2022. All species of the Plagiochilaceae were collected using the explorative method, by tracking along the research area. Nine species of Plagiochilaceae were found belonging to one genera Plagiochila. The species found were P. arbuscula, P. bantamensis, P. dendroides, P. denticulata, P. obtusa, P. salacensis, P. sciophila, P. sumatrana, P. ungarangana